RISK ASSESSMENT FOR WORK HEALTH AND SAFETY: A UNIVERSITY DINING HALL - Kübra ÖZDEMIR; Ayşe ÖZDEMIR (Rojan GÜMÜŞ, 2021)
With the development of working life, work health and safety has become an area of great importance. Currently preventing occupational diseases and work accidents that may occur as a result of the work environment or work conditions, and protecting the health, and ensuring the full well-being of working individuals are among important topics. The increase in work accidents linked to the intense workload, rapid growth, and increased employment in the dining hall sector is emerging as a large problem. This research was performed to take precautions to solve problems emerging in terms of work health and safety in the dining hall sector, completed risk analysis to determine hazards and risks in a university dining hall. Precautions and implementations taken about the topic were evaluated within the framework of the Occupational Health and Safety Law No. 6331 by investigation in terms of work health and safety for accidents, risks, and occupational diseases that may occur in the dining hall. This research was performed using the L-type matrix (5 x 5 matrix table) method. The identified hazards and risks were classified according to risk level (significant level of risk: 15, moderate level of risk: 32, the acceptable level of risk: 3). Precautions were determined as a result of the risk assessment in order to make work conditions healthier and safer. With this study, experiences of work accidents and occupational diseases will be prevented contributing to protecting employee health, while benefits will be provided by ensuring awareness in other workplaces. Additionally, it is considered that adopting proactive approaches within the scope of work health and safety is an important factor in terms of popularizing work safety culture in working areas.